Risk Factors for Postextubation Dysphagia: A Systematic Review and Meta‐analysis. (15th December 2020) - McIntyre, Melanie; Chimunda, Timothy; Koppa, Mayank; Dalton, Nathan; Reinders, Hannah; Doeltgen, Sebastian
Abstract : Objectives/Hypothesis: To identify, describe, and where possible meaningfully synthesize the reported risk factors for postextubation dysphagia (PED) in critically ill patients. Study Design: Systematic review and meta‐analysis. Methods: A systematic search of peer‐reviewed and grey literature was conducted in common scientific databases to identify previously evaluated risk factors of PED. Data extraction and risk of bias assessment used a double‐blind approach. Random effects models were used for the meta‐analyses. Meta‐analyses were conducted where sufficient study numbers allowed after accounting for statistical and clinical heterogeneity. Results: Twenty‐five studies were included, which investigated a total of 150 potential risk factors. Of these, 63 risk factors were previously identified by at least one study each as significantly increasing the risk of PED. After accounting for clinical and statistical heterogeneity, only two risk factors were suitable for meta‐analysis, gender, and duration of intubation. In separate meta‐analyses, neither gender (RR 1.00 [0.71, 1.43], I 2  = 0%) nor duration of intubation (RR 1.54 [−0.40, 3.49], I 2  = 0%) were significant predictors of PED. Conclusions: A large number of risk factors for PED have been reported in the literature. However, significant variability in swallowing assessment methods, patient populations, timing of assessment, and duration of intubation prevented meaningful meta‐analyses for the majority of these risk factors. Where meta‐analysis was possible, gender and duration of intubation were not identified as risk factors for PED. We discuss future directions in clinical and research contexts. Laryngoscope, 132:364–374, 2022